Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet - Li, Weihai; Wang, Ying; Yang, Ding (Zootaxa, 2017)
Two new species of the nemourid genus Amphinemura are described based on recent material collected from the Tibet Autonomous Region of China. The new taxa include A. chayuensis sp. nov. and A. hexalobata sp. nov., the latter species is respresented by both sexes. The new species are compared to related taxa.